Characterization of the neuraminidase (NA) polypeptide of the avian influenza virus A/H5N1 strains in poultry collected during 2004 - 2009 in Vietnam - Nga, Nguyễn Thị Bích; Vân, Lương Thị Hồng; Hòa, Lê Thanh (Vietnam Journal of Biotechnology, 2012)
Antigenic polypeptide neuraminidase (NA) of the avian influenza virus A/H5N1 strains possess a highly variable property at the -NH2 terminal, and this is one of the antigenic variation during evolution. The entire nucleotide sequence (1350 bp) of the neuraminidase (NA) coding for 449 deduced amino acids from 11 A/H5N1 strains isolated in different regions of Vietnam were obtained for comparative analysis. The obtained results revealed that the NA nucleotide sequence for 11 A/H5N1 strains  in this study is 1350 bp in length remaining unchanged since 2003; this was resulted by deletion of 60 nucleotides (20 amino acids) from the fragment of strains isolated prior 2003 (1410 bp NA (N1) gene translated for a peptide of 469 amino acids). There were some drift mutations observed in amino acids sequence of NA derived from the strains collected in 2008 and 2009. Based on twelve major variation sites in NA sequences, 24 strains were clarified to three groups: group I: 2008 - 2009; group II: 2006-2007 and group III: 2004 - 2005. Possibly the NA has evolution time by time to possess several important variations that involved in its pathogenicity in order to easily invade, exist and replicate in humans and animals (HPAI, highly pathogenic avian influenza).